Post‐9/11 excess risk of thyroid cancer: Surveillance or exposure?. Issue 10 (22nd June 2021) - van Gerwen, Maaike; Cerutti, Janete M.; Rapp, Joseph; Genden, Eric; Riggins, Gregory J.; Taioli, Emanuela
Abstract: An excess risk of thyroid cancer has been reported in different World Trade Center (WTC)‐dust exposed cohorts. Increased surveillance of these cohorts has been suggested as a potential explanation of this reported excess thyroid cancer risk leading to an increased diagnosis of earlier‐stage thyroid cancers. However, the uncertainty to what extent surveillance or physician bias may be contributing to the reported incidence of thyroid cancer in WTC‐dust exposed populations remains, highlighting the need to investigate a potential causal link between WTC dust exposure and thyroid cancer. Future studies are therefore indicated to investigate potential consequences of WTC dust exposure on the thyroid gland. Studies of the heavily exposed populations offer the possibility to better understand the mechanisms behind the exposure to a variety of environmental contaminants, and may provide useful insights into exposures harmful to the thyroid. These can be used in risk stratification when implementing screening in high‐risk populations and may inform shared decision‐making regarding the extent of thyroid cancer treatment.